Teaching futsal in schools: perspectives of teachers from Rio Grande do Sul and São Paulo state - Cesar Vieira Marques Filho; Luís Felipe Nogueira-Silva; Larissa Rafaela Gallati; Alcides José Scaglia; Paulo Cesar Montagner (Universidade Estadual Paulista (UNESP), 2021)
Abstract Aim: This study aimed to better understand the perceptions, actions, and interventions of Physical Education teachers at public state schools in the Rio Grande do Sul and São Paulo, regarding didactic-methodological spectra in futsal classes In Brazil, futsal is part of the team sport that must be presented in Physical Education classes, according to educational regulatory documents. Methods: Semi-structured interviews were conducted with eight teachers (three women and one man in each state), whose content was explored through a thematic analysis. Results: The results show a strong singularity of futsal as the content of Physical Education in schools and the relationship with its cultural impact. Different teaching concepts and methodologies used by teachers were identified, as well as a strong connection between experiences with futsal of students and the pedagogical practices adopted. Gender issues were highlighted, showing a contradiction between motivation to change the scenario and a school classes organization that promotes its maintenance. Conclusion: The study supports discussions about teacher actions epistemologically based on traditional teaching perspectives.